Role of ER stress in cystic fibrosis airway inflammation - Ribeiro, Carla Maria Pedrosa (Henry Stewart Talks, 2012)
Pathophysiology: abnormal rheology of airway secretions, Impaired mucociliary clearance, Airway obstruction, Persistent lung infections and inflammation, Respiratory failure, Progressive lung disease as the main cause of death, Role of ER stress responses in CF airways inflammation, Studies on the mechanism of ER stress activation-mediated airway cytokine secretion